S37. A surprising diagnosis of a longstanding leg weakness. (May 2018) - Treidler, Simona O.; Veerapandiyan, Aravindhan; Logigian, Eric; Stanton, Michael
Abstract : Introduction: Multifocal acquired demyelinating sensory and motor (MADSAM) neuropathy is an asymmetric variant of chronic inflammatory demyelinating polyradiculoneuropathy. It presents with multifocal motor and sensory deficits, typically affecting the arms initially and the legs subsequently. Tinel's sign is frequently elicited at the sites of disease. Nerve conduction studies (NCS) are characterized by evidence of focal demyelination. Spinal fluid often reveals mild to moderate increase of protein. Anti-GM1 antibodies can be present but never in a high titer. Sural nerve biopsy may reveal demyelinating changes. MADSAM responds to intravenous immunoglobulin and in 40% of cases to steroids. Methods: Chart review. Results: 52-year-old woman presented with a 10-year history of progressive right leg weakness. She had frequent muscle cramps in the right leg and numbness up to the knee. She denied low back pain, left leg weakness, urinary or bowel symptoms. The neurological examination revealed muscle atrophy of the left forearm and hand, as well as the right posterior thigh and calf. She had no fasciculations. Muscle strength testing of the left hand revealed the following: wrist flexors 4+/5, wrist extensors 4/5, distal finger flexors 4+/5, finger abductors 4−/5, thumb flexor 3/5 and thumb abductor 4/5; and that of the right leg showed: right hip extensor 3/5, knee flexor 4−/5, ankle plantar flexion 2/5, dorsiflexion 5/5, inversion 4−/5, eversion 5/5 and toes extension 5/5. The right arm and left leg examination was unremarkable. Deep tendon reflexes were preserved except for the right ankle jerk which was absent. Sensory examination disclosed only a right-sided pinprick gradient from the toes to the mid-foot. Serum protein electrophoresis with immunofixation was normal and anti-GM1 antibodies were absent. Lumbar spine MRI was unremarkable. MRI of the right leg showed atrophy of the posterior compartment of the thigh and proximal calf. Nerve conduction studies revealed partial conduction block and temporal dispersion of left ulnar and bilateral median motor responses in the forearm, mild median motor conduction slowing through the forearms, an absent right tibial motor response, and absent sural sensory responses. The abnormal sensory responses argue against multifocal motor neuropathy. These findings were interpreted as being consistent with MADSAM with secondary axonal loss particularly in the leg where motor and sensory responses were unevocable. Conclusion: MADSAM typically presents with upper limbs weakness. The striking feature in this patient was the longstanding right leg weakness which overshadowed the left hand weakness. The importance of more extensive clinical and electrodiagnostic evaluation in patients presenting with focal neurological complaints is born out in this patient in whom diagnostic demyelinative findings were evident only in the less affected upper limbs.